2002
DOI: 10.1063/1.1463397
|View full text |Cite
|
Sign up to set email alerts
|

Blue cooperative luminescence in Yb3+-doped tellurite glasses excited at 1.064 μm

Abstract: Blue luminescence emission around 480 nm through cooperative upconversion from pairs of Yb 3ϩ ions implanted into 60TeO 2 -10GeO 2 -10K 2 O-10Li 2 O-10Nb 2 O 5 tellurite glasses and excited by a cw laser at 1.064 m is demonstrated. Cooperative luminescence emission enhancement owing to the temperature dependent multiphonon-assisted anti-Stokes excitation process of the ytterbium ions is also observed. The experimental results revealed a fourfold enhancement in the cooperative luminescence emission when the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…This implies that the short wavelength shift CL is caused by simultaneous radiation transition of excited Yb 3+ ion-pairs accompanied by the absorption of Si-O lattice vibration phonons. 28 We proposed an energy level diagram to explain the process, as shown in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…This implies that the short wavelength shift CL is caused by simultaneous radiation transition of excited Yb 3+ ion-pairs accompanied by the absorption of Si-O lattice vibration phonons. 28 We proposed an energy level diagram to explain the process, as shown in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…4 High brightness emission around 800 nm was recorded besides weaker emissions in the blue and red. Studies of blue cooperative luminescence in Yb 3ϩ -doped TG excited in the infrared was reported 5 and the contribution of optical phonons for the process was exploited to obtain enhancement of the upconversion process. More recently, large upconversion enhancement due to Tm 3ϩ was observed in samples codoped with Nd 3ϩ .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] An important characteristic of these materials is the relatively low cutoff phonon energy compared with other oxide glasses such as silicate or phosphate glasses. This property has motivated a large number of experiments dedicated to the study of the optical properties of TG doped with RE ions, and thus these glasses are revealed to be strong candidates for uses in photonic devices.…”
Section: Introductionmentioning
confidence: 99%
“…But in fact, this is different from what was seen in the experiment. The only physical reason which explains this experimental fact is the energy expansion that results from energy resonant migration among Yb 3+ ions [21,22] . The Yb 3+ concentrations in the Tm(0.1)Yb(5) : FOV samples are 5%, which are pretty high.…”
Section: Characteristic Upconversion Luminescence Satuation Phenomenonmentioning
confidence: 88%
“…So, there surely does not exist the single-photon ground absorption from 3 H 6 level of Tm 3+ . Meanwhile, the released energy from { 2 F 5/2 (Yb 3+ )→ 2 F 7/2 (Yb 3+ )} energy transfer is around 1006 nm (9941 cm −1 ) [21] . Thus, there is a strong first-step energy transfer { 2 F 5/2 (Yb 3+ )→ 2 F 7/2 (Yb 3+ ), 3 H 6 (Tm 3+ )→ 3 H 5 (Tm 3+ )}, because the population of Tm 3+ ion ground state is large, the doubly reduced matrix elements of tensor operators U t between 3 H 6 (Tm 3+ ) and 3 H 5 (Tm 3+ ) state are large [23,24] , and the energy mismatch is about 1545 cm −1 .…”
Section: Upconversion Mechanismmentioning
confidence: 99%